Immunophenotyping in routine clinical practice for predicting treatment response and adverse events in patients with MS - Tobias Zrzavy; Tobias Zrzavy; Kerstin Rieder; Kerstin Rieder; Viktoria Wuketich; Viktoria Wuketich; Renate Thalhammer; Helmuth Haslacher; Patrick Altmann; Patrick Altmann; Barbara Kornek; Barbara Kornek; et al. (Frontiers in Neurology, 2024)
BackgroundRecent studies proposed cellular immunoprofiling as a surrogate for predicting treatment response and/or stratifying the occurrence of adverse events (AEs) in persons with multiple sclerosis (pwMS). However, applicability in real-world circumstances is not sufficiently addressed.ObjectiveWe aimed to explore whether standard routine clinical leukocyte phenotyping before treatment initiation could help stratify patients according to treatment response or AEs in a real-world MS cohort.MethodsIn this retrospective study, 150 pwMS were included, who had been newly initiated on a disease-modifying drug (DMD) and had been assessed for standard immunophenotyping before DMD initiation (baseline) and at least once during the following year. Multivariate models were used to assess an association of immune subsets and the association between immune cell profiles regarding treatment response and AEs.ResultsWe found that the composition of T cell subsets was associated with relapse activity, as an increased proportion of CD8+ lymphocytes at baseline indicated a higher likelihood of subsequent relapse (about 9% per 1% increase in CD8+ proportion of all CD3+ cells). This was particularly driven by patients receiving anti-CD20 therapy, where also EDSS worsening was associated with a higher number of CD8+ cells at baseline (3% increase per 10 cells). In the overall cohort, an increase in the proportion of NK cells was associated with a higher risk of EDSS worsening (5% per 1% increase). Occurrence of AEs was associated with a higher percentage of T cells and a lower number of percentual NKT cells at baseline.ConclusionImmune cell profiles are associated with treatment response and the occurrence of AEs in pwMS. Hence, immunophenotyping may serve as a valuable biomarker to enable individually tailored treatment strategies in pwMS.